Indonesian Consumers’ Intention of Adopting Islamic Financial Technology Services - Purwantini, Anissa Hakim; Noor Athief, Fauzul Hanif; Waharini, Faqiatul Mariya (Shirkah: Journal of Economics and Business, 2020)
With the rise of Halal Lifestyle in the digital era, Islamic Financial Technology (henceforth FinTech) has increasingly become impactful to economic growth. Islamic FinTech companies are in a dire need to figure out factors that influence the adoption and acceptance of the technology to promote their business. Addressing the issue, this study examines consumers’ intention of using Islamic Fintech services. An online survey was employed to elicit the required data from 75 Indonesian consumers of Islamic FinTech services. The results of data analysis by means of SEM-PLS depicted that perceived usefulness and interpersonal influence were two key factors driving the consumers to use Islamic FinTech services. The results further revealed that compatibility positively influenced perceived usefulness and perceived ease of use, which in turn, affected the consumers’ attitude. Moreover, it was also noted that attitude and internet self-efficacy as perceived behavioral control in decomposition of theory of planned behavior had no significant impact on consumers’ intention. The results of this study theoretically provide a basic model of consumers’ intention in the context of Islamic FinTech. At the same time, FinTech industry users can use the results of the present study as references to come up with appropriate strategy to deal with the market needs.